Social Isolation and Sleep: Manifestation During COVID-19 Quarantines - Pilcher, June J.; Dorsey, Logan L.; Galloway, Samantha M.; Erikson, Dylan N. (Frontiers in Psychology, 2022)
Although researchers have investigated the impact of social isolation on well-being, the recent quarantines due to COVID-19 resulted in a social isolation environment that was unique to any examined in the past. Because sleep is an endogenous drive that impacts short- and long-term health and well-being, it is important to consider how social isolation during the COVID-19 government-mandated quarantines affected sleep and sleep habits. A number of researchers have addressed this question during the last two years by examining several sleep-related outcomes during the quarantines. To best understand these recent results, the current mini review provides a background on the pre-pandemic literature on the effects of social isolation and loneliness with a focus on sleep and then summarizes the recent literature on sleep and sleep habits during the COVID-19 quarantines. In general, sleep was negatively impacted for many people during the pandemics but not for everyone. One group that seemed to benefit from the pandemic in terms of sleep patterns, were younger people who could more easily adapt their sleep times to match their internal chronobiology. Given the potential broad impact of sleep on health and well-being, better understanding how social isolation impacts sleep is an important consideration for individuals, organizations, and governments.